2014
DOI: 10.1016/j.chembiol.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observations of Amyloid β Self-Assembly in Live Cells Provide Insights into Differences in the Kinetics of Aβ(1–40) and Aβ(1–42) Aggregation

Abstract: SummaryInsight into how amyloid β (Aβ) aggregation occurs in vivo is vital for understanding the molecular pathways that underlie Alzheimer’s disease and requires new techniques that provide detailed kinetic and mechanistic information. Using noninvasive fluorescence lifetime recordings, we imaged the formation of Aβ(1–40) and Aβ(1–42) aggregates in live cells. For both peptides, the cellular uptake via endocytosis is rapid and spontaneous. They are then retained in lysosomes, where their accumulation leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
133
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 42 publications
(47 reference statements)
9
133
1
1
Order By: Relevance
“…Compact amyloid aggregates were observed for both alloforms. (486) While, these experiments represent one step ahead towards understanding aggregation in the cells, higher spatial resolution methods and how the cellular environment affects the dynamics of Aβ1-40/42 and their variants are major concerns. To this end, in cell-NMR of Aβ protein is an ideal tool for gaining information at the atomic level, but several obstacles remain.…”
Section: Discussionmentioning
confidence: 99%
“…Compact amyloid aggregates were observed for both alloforms. (486) While, these experiments represent one step ahead towards understanding aggregation in the cells, higher spatial resolution methods and how the cellular environment affects the dynamics of Aβ1-40/42 and their variants are major concerns. To this end, in cell-NMR of Aβ protein is an ideal tool for gaining information at the atomic level, but several obstacles remain.…”
Section: Discussionmentioning
confidence: 99%
“…However, Esbjörner et al . used fluorescence lifetime imaging to monitor amyloid formation in living cells, and they found that both A β 40 and A β 42 were ingested by cell via endocytosis. More researches are required to understand the difference of A β 40 and A β 42 in cellular uptake pathways.…”
Section: Metabolism Of Aβ42 and Aβ40mentioning
confidence: 99%
“…For applications in cell biology and molecular self-assembly reactions [7][8][9][10][11][12] that require imaging with high temporal resolution over many time points, structured illumination microscopy (SIM) can be well-suited as it is not dependent on the photophysical properties of a particular fluorescent probe. Despite this inherent advantage of SIM, up to now its use has been mainly confined to imaging fixed cells or slow moving processes.…”
Section: Introductionmentioning
confidence: 99%